The Controversy over Marine Protected Areas - Caveen, Alex (Springer, 2015)
This book is a critical analysis of the concept of marine protected areas (MPAs) particularly as a tool for marine resource management. It explains the reasons for the extraordinary rise of MPAs to the top of the political agenda for marine policy, and evaluates the scientific credentials for the unprecedented popularity of this management option. The book reveals the role played by two policy networks - epistemic community and advocacy coalition - in promoting the notion of MPA, showing how advocacy for marine reserves by some scientists based on limited evidence of fisheries benefits has led.